SISTEM INFORMASI PENGOLAHAN DATA SISWA BERBASIS WEB PADA RA AN-NASYWA (STUDI KASUS PENGOLAHAN DATA SISWA): DFD (Data Flow Diagram);Input;Output;Phpmyadmin;Student Data Management System. - Djauhari, Teuku; Irfandi, Baso (JURNAL AKADEMIKA, 2022)
RaudhatulAtfhal An-Nasywa Kindergarten School is an early childhood education school that is 4-6 years old, currently RaudhatulAtfhal An-Nasywa Kindergarten is still doing it manually with books in managing student data and grades. So we need a student data management information system that can increase the speed and accuracy in processing student data. The basic purpose of making a student data processing information system is to make it easier to manage data. Making this student processing information system using system design and database design. The student data processing information system uses PHP MyAdmin as a data storage medium. Student data processing information system that will be used by administrators to enter the data needed to perform data processing. The final result of the research was found that by building an information system for processing student data at the RaudhatulAtfhal An-Nasywa Kindergarten School, it could be more helpful for the school where previously student data and other documents were still in conventional form.